Excess Screen Time - Impact on Childhood Development and Management: A Review - Karki, Utkarsh; Sravanti, Lakshmi (Med Phoenix, 2021)
In recent years children are immersed in both traditional and new forms of digital media around the globe. Screen time is now embedded in the daily lives of young children beginning from infancy. Pre-schoolers exposed to screen and interactive media may benefit in many ways but excessive and inappropriate screen exposure could potentially lead to several health and developmental risks. Environmental factors such as parents, siblings, peers have a profound influence on a child’s development. Despite challenges of screen media parenting practices and those posed by lockdown (work from home, online schooling) during this pandemic, parents hold the key to navigate these challenges by serving as role models to ensure positive developmental outcomes in their children.